A Randomized Controlled Trial of mHealth Mindfulness Intervention for Cancer Patients and Informal Cancer Caregivers: A Feasibility Study Within an Integrated Health Care Delivery System. (May 2019) - Kubo, Ai; Kurtovich, Elaine; McGinnis, MegAnn; Aghaee, Sara; Altschuler, Andrea; Quesenberry, Charles; Kolevska, Tatjana; Avins, Andrew L.
Purpose: To assess feasibility and preliminary efficacy of a mobile/online-based (mHealth) mindfulness intervention for cancer patients and their caregivers to reduce distress and improve quality of life (QoL).Material and Methods: Two-arm randomized controlled trial within Kaiser Permanente Northern California targeting cancer patients who received chemotherapy and their informal caregivers. The intervention group received a commercially available mindfulness program for 8 weeks. The wait-list control group received usual care. We assessed feasibility using retention and adherence rates and obtained participant-reported data on distress, QoL, sleep, mindfulness, and posttraumatic growth before and immediately after the intervention.Results: Ninety-seven patients (median age 59 years; female 69%; 65% whites) and 31 caregivers (median age 63 years; female 58%; 77% whites) were randomized. Among randomized participants, 74% of the patients and 84% of the caregivers completed the study. Among those in the intervention arm who initiated the mindfulness program, 65% practiced at least 50% of the days during the intervention period. We observed significantly greater improvement in QoL among patients in the intervention arm compared with controls. Caregivers in the intervention group experienced increased mindfulness compared with controls. Participants appreciated the convenience of the intervention and the mindfulness skills they obtained from the program.Conclusion: We demonstrated the feasibility of conducting a randomized trial of an mHealth mindfulness intervention for cancer patients and their informal caregivers. Results from fully powered efficacy trials would inform the potential for clinicians to use this scalable intervention to help improve QoL of those affected by cancer and their caregivers.